Exploration of the Application of the Peer Tutoring Method to Improve Reading Skills of Fourth Grade Students: A Case Study at SDN Tanjung Waras: Implementation of Peer Tutoring Method to Improve Reading Skills - Enni Maria; Endang Susilowati (Creative Smart Visionary, 2025)
The low reading skills of some fourth-grade students at Tanjung Waras Public Elementary School require more effective and supportive learning strategies. This study aims to evaluate the implementation of the peer tutoring method in improving reading skills and examine its impact on students' motivation and social dynamics. The study used a descriptive case study approach with stages of diagnostic assessment, implementation of peer tutoring through the